2020
DOI: 10.1155/2020/3562753
|View full text |Cite
|
Sign up to set email alerts
|

The Sufficient Immunoregulatory Effect of Autologous Bone Marrow-Derived Mesenchymal Stem Cell Transplantation on Regulatory T Cells in Patients with Refractory Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an advanced autoimmune disease described by joint involvement. The special properties of mesenchymal stem cells (MSCs) introduced them as a potential therapeutic candidate for RA. In this study, a single dose of autologous MSCs isolated from bone marrow (autologous BM-MSCs, 1×106 per kg) was injected intravenously into 13 patients suffering from refractory RA who were followed up within 12 months after the intervention to evaluate immunological elements. Our results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
0
31
1
Order By: Relevance
“…A significant decrease in DAS28-ESR, VAS, and ESR up to 12 months was reported [ 43 ]. In contrast to previous clinical trials using MSC-based therapy for RA, no statistically significant differences in serum levels of CRP, anti-CCP, IL-17, and IFN-γ cytokine levels were observed [ 43 , 87 ]. A significant increase in the percentage of regulatory CD4 + T cells one month after MSC infusion was observed.…”
Section: Clinical Studiescontrasting
confidence: 84%
See 2 more Smart Citations
“…A significant decrease in DAS28-ESR, VAS, and ESR up to 12 months was reported [ 43 ]. In contrast to previous clinical trials using MSC-based therapy for RA, no statistically significant differences in serum levels of CRP, anti-CCP, IL-17, and IFN-γ cytokine levels were observed [ 43 , 87 ]. A significant increase in the percentage of regulatory CD4 + T cells one month after MSC infusion was observed.…”
Section: Clinical Studiescontrasting
confidence: 84%
“…A significant increase in the percentage of regulatory CD4 + T cells one month after MSC infusion was observed. The increase of regulatory CD4 + T cells measured by FOXP3 mRNA levels was maintained in parallel to an increase in T-bet and GATA3 transcription factor mRNA levels and IL-10 and TGF-β cytokine levels in the sera 12 months after the MSC infusion [ 87 ]. The authors suggested that the decrease in percentage of regulatory CD4 + T cells in the periphery following MSC infusion suggests that multiple infusions of MSCs or higher dose of MSCs may be required to sustain expansion of in vivo regulatory CD4 + T cells.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve-month follow-up showed no adverse effect, a significant decrease in DAS28-ESR, VAS scores and ESR, but no changes in blood inflammatory markers ( 169 ). Systemic injection of autologous BM-MSCs into refractory RA patients with 12 month-follow up demonstrated that the gene expression of forkhead box P3 (FOXP3) in peripheral blood mononuclear cells (PBMCs) was significantly induced ( 170 ). Furthermore, high levels of IL-10 and transforming growth factor-beta 1 (TGF-β1) were noted in the culture supernatant of PBMCs over the time course of treatment ( 170 ).…”
Section: Therapeutic Use Of Mscs In Ra and Slementioning
confidence: 99%
“…Systemic injection of autologous BM-MSCs into refractory RA patients with 12 month-follow up demonstrated that the gene expression of forkhead box P3 (FOXP3) in peripheral blood mononuclear cells (PBMCs) was significantly induced ( 170 ). Furthermore, high levels of IL-10 and transforming growth factor-beta 1 (TGF-β1) were noted in the culture supernatant of PBMCs over the time course of treatment ( 170 ). Autologous BM-MSCs were also used in another study with promising effects, but up to 12 months follow up ( 171 ).…”
Section: Therapeutic Use Of Mscs In Ra and Slementioning
confidence: 99%